A Rare Case of Immune Reconstitution Inflammatory Syndrome Development in an Immunocompromised Patient with Progressive Multifocal Leukoencephalopathy and Multicentric Castleman's Disease. (19th August 2013) - Kurukumbi, Mohankumar; Steiner, Sheldon; Dunlap, Shariff; Chapman, Sherita; Solieman, Noha; Jayam-Trouth, Annapurni
Abstract : Immune reconstitution inflammatory syndrome (IRIS) development in HIV with preexistent progressive multifocal leukoencephalopathy (PML) has been extensively studied. PML-IRIS typically manifests clinically as new or worsening neurologic symptoms in conjunction with enlarging CNS lesions and occurs in approximately 10–20 percent of HIV-infected patients with PML who begin HAART. Likewise, Multicentric Castleman's Disease (MCD), a rare malignant lymphoproliferative disorder, has a strong and well-known association with HIV. Our case provides a rare instance of PML-IRIS in combination with MCD in an HIV-positive individual. The combination of all three diseases has never been reported in the literature. Both MCD and PML were present during initial determination of HIV infection in our patient and their disease courses were altered during the subsequent development of IRIS.